A Design Of Mini Doppler Detector Circuit System For Human Heartbeat Control - Mei Winda Siagian; Solly Aryza; Zuraidah Tharo (Jurnal Scientia, 2024)
Fetal Doppler is a tool used to detect the fetal heartbeat in the womb. This tool is widely used in maternity clinics or for mothers who want to hear the sound of the baby's heartbeat in their womb. With this tool, the development of the fetus in the womb can be monitored so that the health of the fetus in the womb remains healthy. The mini Doppler detector circuit has been successfully designed with the expected output results, namely being able to detect frequencies of 2 to 3 Hz. So this circuit can be realized for a mini doppler detector.